Update to the Quaternary Stratigraphic Division in Xiaoshao Plain, Zhejiang, China - Liu, Jiawei; Xing, Lu; Shao, Caijun; Li, Shaohe; Huang, Man; Weng, Jian; Fu, Chengcheng (Journal of coastal research, 2023)
Liu, J.; Xing, L.; Shao, C.; Li, S.; Huang, M.; Weng, J., and Fu, C., 2023. Update to the Quaternary stratigraphic division in Xiaoshao Plain, Zhejiang, China. Journal of Coastal Research, 39(5), 984–997. Charlotte (North Carolina), ISSN 0749-0208. Establishing a reliable chronological framework of Quaternary sedimentary stratigraphy contributes to a more comprehensive understanding of the evolutionary patterns of sedimentary environments and predicts their trends. Local exploration standards are essential indicators in the construction of a chronological framework for Quaternary sedimentary stratigraphy. However, many of the local standards introduced today lack detailed field investigations and comprehensive and in-depth analyses of geological investigations in local areas and still need further improvement. For these areas, there are significant differences in understanding between different researchers, and the absence of appropriate and uniform local standards will lead to misjudgment of geological conditions and cause much inconvenience in the design, construction, and management of engineering and construction projects. On the basis of this, Xiaoshao Plain in Zhejiang Province, China serves as a research subject and samples were collected by drilling and coring. The Quaternary stratigraphy of Xiaoshao Plain is tentatively divided into nine major layers and 22 sublayers following the local standard of Zhejiang Province's Code for Geotechnical Engineering Investigation of Engineering Construction (DB33/1065-2009) introduced in 2009. The geological age of some of the strata in the area and changes in the depositional environment were further explored through accelerator mass spectrometry (AMS) 14C testing and microsomal paleontological fossil identification. Thus, the large stratigraphy of the Quaternary sedimentary strata of Xiaoshao Plain in the Zhejiang local standard is supplemented. Finally, in combination with the existing regional engineering geological survey report, the stratigraphic substratum of the area has been reclassified (the study divides it into 36 substrata). This study provides new ideas for the improvement of local standards for geological surveys and guidance for engineering construction development in Xiaoshao Plain.